(Invited) Multimodal Enzymatic Sensing for Continuous Wound Monitoring. (13th December 2018) - RoyChoudhury, Sohini; Bhushan, Pulak; Umasankar, Yogeswaran; Hirt, Penelope A.; Lev-Tov, Hadar A.; Kirsner, Robert S.; Bhansali, Shekhar
Abstract : Present wound care is primarily visual, entailing repeated clinical trips. A biosensing system offering direct longitudinal measures of healing can assist to bridge the time between occurrence of wounds and their management. Purine metabolites, xanthine and uric acid, are known to have high correlation with wound chronicity and healing. With increased apoptosis, concentrations of these analytes reportedly increase. In this study, their biochemical pathways in purine metabolism are explored to provide a method to monitor healing on a multimodal sensing platform. This work employs enzymes xanthine oxidase and uricase, for detection of uric acid and xanthine respectively. pH of wounds change with healing, from alkaline to acidic, shifting the potential of detection. Effects of pH have been investigated on the same platform enabling real-time calibration, attempting to provide improved assessment of tissue recovery. Nanomaterials of carbon (C) and gold (Au) have been utilized here, to improve the sensitivity of detection.